Exploring social-ecological impacts on trade-offs and synergies among ecosystem services - Wang, Xiaoyu; Peng, Jian; Luo, Yuhang; Qiu, Sijing; Dong, Jianquan; Zhang, Zimo; Vercruysse, Kim; Grabowski, Robert C.; Meersmans, Jeroen (Elsevier, 2022)
An in-depth understanding of the complex patterns of ecosystem services (ESs) interactions (i.e., synergies or trade-offs) based on social-ecological conditions is an important prerequisite for achieving sustainable and multifunctional landscapes. This study aimed to explore how ESs interactions are influenced by social-ecological factors. Taking the Sutlej-Beas River Basin as a case study area, where the linkages between ESs interactions and social-ecological processes are poorly understood, ESs interactions were identified through principal component analysis and correlated with a range of social-ecological factors, which were explored spatially based on ES bundles. The results revealed two dominant types of ESs interactions, namely multifunctionality-related synergies and grain production-related trade-offs. Population, nighttime light, precipitation, temperature, and soil clay content were all positively correlated with the two ESs interactions. Contrarily, elevation and soil sand content were negatively correlated with the two ESs interactions. Four main ES bundles were identified, which spatially describe the presence of ESs synergies and/or trade-offs in relation to social-ecological factors. This study provides a feasible way to explore the spatial differentiation and influencing factors impacting the interactions between ESs, which can provide a basis for an integrated watershed-based management of ESs.
Keywords: Ecosystem service trade-offs and synergies; Ecosystem service bundles; Social-ecological impacts